Grundtvigs forhold til Sverige - Nielsen, Valdemar (Grundtvig-studier, 1970)
“ Grundtvig’s Relations with Sweden” By Valdemar Nielsen In continuation and conclusion of two previous papers by the same writer (printed in Gr.-St. 1958 and 1961) this paper from the annual meeting at Kungälv, 1969, gives an account of the various attempts during Grundtvig’s lifetime to bring about a meeting between Grundtvig and the Swedes who might be assumed to be interested in his thoughts. A number of conditions making the development in Sweden distinct from the contemporaneous development in Denmark are adduced to explain why the attempts failed each time.When in 1810 the Swedes elected marshal Bemadotte successor to the Throne instead of Frederik VI, and the former, in 1814, took the opportunity to become King of Norway too, Grundtvig spoke about this course of action in very harsh words. In Kort Begreb af Verdens Krønike (The History of the World) from 1812 Grundtvig’s comments on the organisation of the Swedish Church after the Reformation are very critical too; but in 1816 he wrote a very appreciatory article on a circular letter by the Swedish archbishop. In 1817 he corresponded with A. A. Afzelius, the Swedish Court chaplain, who visited Grundtvig in Copenhagen in 1845 and wrote an account of his visit. The reason why Grundtvig’s connection with P. Wieselgren, the dean of Gothenburg, did not result in a wider dissemination of Grundtvig’s thoughts may be the vastly different attitude to problems that Wieselgren, as a reader in Lund, expressed in his book Hvilken är Sveriges religion? (What is Sweden’s Religion) (1827). L1 book he distinguishes between “ Bible Christianity” and “confessional Christianity”, by which he means that now the Bible was a guide to understanding the symbolic books authorised by the church, now the symbolic books guided the understanding of the Bible in Sweden. Wieselgren sent Grundtvig a copy of the book, asking him to comment on it, but he never did so in writing, although Wieselgren visited him two years later. Nor did Grundtvig bring his influence to bear in 1845 when his intervention might have had a salutary effect on the fight between the Swedish revival movements and the high church. He did not comply with Wieselgren’s direct request that he should become “the reformer of the Scandinavian Church”.But Grundtvig’s ideas of a learned union between the three Scandinavian countries have evoked a certain real response in Sweden, and have been carried through to a certain extent. First by the establishment of the University of Gothenburg, then by the establishment of the Nordic Folk High School at Kungälv, then by the annual meetings of the Nordic Summer University, and finally by the establishment of the Scandinavian Peoples’ Academy at Kungälv, where the annual meeting of the Grundtvig Society was held in 1969.Even though Grundtvig himself never availed himself of any of the opportunities he had to address a Swedish audience, his thoughts have inspired both debate and reflection in Sweden. But strange as it may seem he is not even mentioned in the monumental work En bok om kyrkan (A book about the Church) (1943), to which Professor Anton Fridrichsen, who admired Grundtvig highly, contributed two articles. Elsewhere (in Nordisk Tidskrift, 1942) he mentions Vilh. Grønbech’s statement that Grundtvig created a new religion, but he adds, “what Grønbech is referring to as new is old in Christianity, in fact the oldest part of it.” He looked upon Grundtvig as a guide, on a equal footing with Luther, to “the new interpretation of Christ and the new attitude to the church for which the age is thirsting and for which the church is striving.” After having mentioned Carstensen’s, Aronson’s, and Wentz’s works on Grundtvig Valdemar Nielsen concluded by quoting the poem by Hostrup in which it is said that Grundtvig inspires controversy because he touches upon fundamentals. This is still true about his relations with Sweden, even 100 years after his death.